AN EXPLORATION TO CHRISTIANITY TEACHING CONCERNING PENAL MEDIATION OF CRIMINAL PROCEDURE LAW IN INDONESIA - Christar Arstilo Rumbay; Halim Wiryadinata (Justitia et Pax, 2021)
Civil court justice shares the nature of mediation as part of litigation process. However, criminal procedure code does not accommodate penal mediation by litigation and non-litigation process. Therefore, penal mediation is considered as an Alternative Dispute Resolution in criminal law. This article attempts to build conversation between jurisprudence and theology, especially speaking the nature of mediatorship of Christian teaching that could be considered as beneficial donates for future penal mediation in criminal law in Indonesia. This research is qualitative work. Literatures, articles, books and related references will receive attention. In conclusion, penal mediation applies to litigation and non-litigation tract, the state should conduct its implementation, modern law maintains its legacy, Christology serves the initiation, and penal mediation pursues restorative justice.